ОБЩЕЕ НЕПРЕРЫВНОЕ РЕШЕНИЕ СИСТЕМ ЛИНЕЙНЫХ РАЗНОСТНЫХ УРАВНЕНИЙ С 1-ПЕРЕОДИЧЕСКИМИ КОЭФФИЦИЕНТАМИ - Тураев, Х.; Эштурсунов, М.; Норкобилов, Х. (SCIENCE and SOCIETY, 2025)
This work studies the problems of constructing continuous solutions of a system of linear differential equations of the form x(t+1)=A(t)x(t)+B(t) with coefficients equal to 1. Here t∈R=(-∞,+∞), A(t) is a real continuous n×n matrix with period 1, B(t) is a real n-dimensional vector with period 1.
Keywords: general; continuous; solution; equation; matrix; periodic; dimension; differential equation; dimension of matrix